Anti-Parkinson’s Potential Of Acorus Calamus Linn: A Review (Journal of Pharmaceutical Negative Results, 2022)
Acorus calamus Linn is a species of perennial, semi aquatic, aromatic herb with creeping rhizomes; it belongs to the family Acoraceae. In Ayurveda Acorus calamus Linn is also known as VACHA and publically known as Bacha or sweet flag. It is a highly valued herb as it acts as a rejuvenator for brain and nervous system. It is a main medhya drug, which has the property of improving the memory power and intellect. Acorus calamus (AC) has been used as traditional Indian and Chinese prescriptions for its beneficial effects on cognitive and memory enhancement, anti-aging and anticholinergic activity. Scientific-asarone possessed to have antidepressant, anticonvulsant, anti-inflammatory, analgesic, antipyretic, antispasmodic, cytoprotective, immunomodulatory, antidiarrheal, antimicrobial,  and studies reported AC and its active constituents anthelmintic, insecticidal, and hypolipidemic effects. This review presents a pragmatic description that deals with chemical constituents and neuropharmacological properties of Acorus calamus for easy and better understanding of the outstanding medicinal potential of this very special plant.